Dexmedetomidine protects hepatic cells against oxygen‐glucose deprivation/reperfusion injury via lncRNA CCAT1. (2nd July 2018) - Zhou, Zhuang; Chen, Qingsong; Wan, Lei; Zheng, Daofeng; Li, Zhongtang; Wu, Zhongjun
Abstract: Dexmedetomidine (Dex) protects different cell types during hypoxia or ischemia‐reperfusion injury by inhibiting cell apoptosis. However, the underlying mechanism and its impact on hepatic ischemia reperfusion injury are still not known. In this study, we established a model of oxygen‐glucose deprivation/reperfusion (OGD/R) injury in hepatocyte HL7702 cells, and studied the impact of Dex on cell proliferation, apoptosis, and cell cycle during OGD/R. In addition, we explored the role of CCAT1 in this process. We found that Dex increased cell proliferation and inhibited cell apoptosis during OGD/R, in a concentration‐dependent manner. Dex partially reversed the OGD‐inhibited expression of lncRNA CCAT1. Knockdown of CCAT1 by siRNA inhibited Dex‐mediated protection against OGD/R‐induced injury and promoted cell apoptosis, caspase‐3 expression and cell cycle arrest in the G0/G1 phase, and inhibited cell proliferation and cyclin D1 expression. In contrast, overexpression of CCAT1 by pcDNA3.0‐CCAT1 enhanced Dex‐mediated protection against OGD/R‐induced cell injury. Thus, Dex protects hepatocytes against OGD/R injury by upregulating lncRNA CCAT1. This study suggests a novel role of CCAT1 in ischemia reperfusion injury, and lays the framework for future studies.